ANALYSIS OF THE ASEAN-U.S. COMPREHENSIVE STRATEGIC PARTNERSHIP (CSP) STRATEGY IN ACCELERATING THE ENERGY TRANSITION IN ASEAN 2021–2024 - Maria Manjur (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2026)
The Southeast Asian region is highly vulnerable to the global climate crisis, characterized by an increase in hydrometeorological disasters and a high dependence on fossil fuels (75%–80%). However, ASEAN faces structural challenges in the form of an energy transition funding gap of up to USD 200 billion and a shortage of workers with green skills. This study aims to analyze the effectiveness of the ASEAN–U.S. Comprehensive Strategic Partnership (CSP) in accelerating the energy transition to support the implementation of SDG Goal 13 (Climate Action) in Southeast Asia during the 2021–2024 period. The research methodology employs a qualitative case study approach with a descriptive-analytical design. Data collection was conducted through in-depth interviews as primary data and documentary analysis (journals, reports from international organizations, official policy documents) as secondary data. Data analysis was conducted systematically through data reduction, data presentation using the Environmental Policy Integration (EPI) Framework, the Kirkpatrick Model, and the UNDP Capacity Framework, and the drawing of conclusions based on Institutional Neoliberalism Theory. The research results indicate that the ASEAN-U.S. CSP strategy has successfully facilitated the scaling up of member states’ NDC targets, supported the strengthening of the ASEAN Centre for Energy’s (ACE) technical capacity in operating the Lao PDR-Thailand-Malaysia-Singapore Power Integration Project (LTMS-PIP) multilateral power interconnection, and channeled green financing through the U.S. Development Finance Corporation (DFC) for clean energy projects in Indonesia, Vietnam, and the Philippines. Nevertheless, its effectiveness remains limited by a massive funding gap. The targeted outputs of this research are scientific articles published in accredited national journals or reputable international journals, as well as policy briefs for strengthening regional climate diplomacy.